Aloe vera-derived extracellular vesicle-like particles suppress pancreatic carcinoma progression through triggering pyroptosis via ROS-GSDMD/E signaling pathway - Jieyu Shen; Tianfu Wei; Mingchen Li; Yuankuan Jiang; Jiahui Zhang; Yueyi Qi; Cai Chen; Xiaojie Li; Peng Huang; Jialin Qu (Chinese Medicine)
Abstract Background Pancreatic carcinoma (PC) remains one of the most aggressive malignancies that is often referred to as the “king of cancers” in clinic. Plant-derived extracellular vesicle-like particles (p-EVLP) has demonstrated broad-spectrum antitumor potential through their unique ability to effectively penetrate tumor microenvironments and deliver bioactive compounds. Aloe Vera is a tender and juicy plant with anti-tumor properties, while whether Aloe Vera-derived EVLP (AV-EVLP) can inhibit PC and what the underlying mechanism is still unclear. Methods Two kinds of AV-EVLPs (EV-U and EV-P) were isolated from Aloe vera using comparative purification techniques. Their structure and composition characterization were performed using TEM, NTA and UHPLC-QTOFMS. In vitro experiments using Panc-1 cells included cytotoxicity, migration/invasion and cellular uptake assay were employed to investigate their tumor inhibition potential. In a Panc-1 xenograft mouse model, the therapeutic effects and systemic toxicity of EV-U were evaluated through tumor volume and weight, Ki67, TUNEL and histopathology examination. Mechanistic studies involved the levels of cellular ROS, IL-1β, IL-18 and the expression of caspase-1/3/7/9-GSDMD/E in both cell and tumor tissues were determined by ELISA, immunohistochemistry, Western blot and qRT-PCR. Results EV-U and EV-P exhibited characteristic cup-shaped morphology with mean diameters 179.3 nm and 227.1 nm, respectively. At their respective IC50 concentrations, both effectively inhibit cell migration and invasion and increase ROS, LDH, IL-18, and IL-1β levels in Panc-1 cells. Comparably, EV-U exhibited better activity due to their fewer impurities and more uniform dispersion. Further in vivo experiments supported the effectiveness of EV-U in reducing tumor volume and weight without causing toxicity or immunogenicity. Mechanistically, the activation of pyroptosis through the caspase-1/3/7/9-GSDMD/E pathways contributed to its efficacy. Conclusion AV-EVLP significantly inhibit pancreatic cancer progression by triggering mitochondrial ROS release through the activation of caspase-1/3/7/9-GSDMD/E-mediated pyroptosis. Graphic Abstract AV-EVLPs effectively inhibited the migration and invasion of Panc-1 cell and reduced tumor volume and weight in Panc-1 tumor-bearing mice, whose mechanism was related to triggering pyroptosis via ROS-GSDMD/E pathways.